2008
DOI: 10.1097/wnf.0b013e31815cba78
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Polypharmacy in Patients With Schizophrenia in a Brief Hospitalization Unit

Abstract: Despite different clinical guidelines, AP is a common pharmacological strategy as it is shown in our study and in the reviewed literature. Data in our study indicate that the observed rates of AP cannot exclusively be attributed to the treatment of patients with clozapine-resistant schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
0
12
2
Order By: Relevance
“…Clinical practice guidelines strongly recommended antipsychotic monotherapy for the treatment of schizophrenia (Barnes 2011; Lerma-Carrillo et al 2008; National Institute for Health and Care Excellence (NICE) 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Clinical practice guidelines strongly recommended antipsychotic monotherapy for the treatment of schizophrenia (Barnes 2011; Lerma-Carrillo et al 2008; National Institute for Health and Care Excellence (NICE) 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, European data on patients diagnosed with schizophrenia and being treated in acute psychiatric units reveal that antipsychotic polypharmacy is a common (if not the most common) strategy and that it is not reserved for the most treatment-resistant cases [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…In our study, dual-psychotic patients were prescribed 3.6 (SD = 1.1) medications. Furthermore, in a retrospective study, Lerma-Carrillo et al (2008) reviewed all the psychotropic drugs dispensed to 209 inpatients diagnosed with schizophrenia or schizoaffective disorder of a brief hospitalization psychiatric unit. In another study, Pandurangi and Dalkilic (2008) described in a meta-analysis that 5% to 39% of psychotic patients consumed 2 or more medications.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Kreyenbuhl et al reported the amount of antipsychotic medications consumed by psychotic patients and they found that 12.8% of psychotic patients took 2 or more antipsychotics. They found that only 45.5% received monotherapy, and the most frequent number of antipsychotic medications prescribed was 2 (range: 1-9) (Lerma-Carrillo et al, 2008). Furthermore, in a retrospective study, Lerma-Carrillo et al (2008) reviewed all the psychotropic drugs dispensed to 209 inpatients diagnosed with schizophrenia or schizoaffective disorder of a brief hospitalization psychiatric unit.…”
Section: Discussionmentioning
confidence: 99%